A history shared and divided : East and West Germany since the 1970s - Bösch, Frank, 1969-; Neuheiser, Jennifer Walcoff (Berghahn, 2018)
"By and large, the histories of East and West Germany have been studied in relative isolation. And yet, for all their differences, the historical trajectories of both nations were interrelated in complex ways, shaped by oil shocks, technological advances, protest movements, and other phenomena so diffuse that they could hardly be contained by the Berlin Wall. Accordingly, Divided History offers a collective portrait of the two Germanies that is both broad and deep. It brings together comprehensive thematic surveys by specialists in politics, media, the environment, and similar topics to assemble a monumental account of both nations from the crises of the 1970s to--and beyond--the reunification era"--